BULEAN: KOMPOSISI MUSIK ORKESTRA - Weldi Syaputra; Wilma Sriwulan; IGN Wiryawan Budhiana (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Musical work called Bulean, an Orchestra Music Composition, is a descriptive programa music. It is inspired by phenomenon occurred on healing ceremony of Talang Mamak tribe in Indragiri Hulu District, Riau. This creation aims at making a programa music that’s able to express phenomenon occurred on Bulean ceremony by using the approach of Western music convention in Orchestra format. This work divided into three parts namely menginang in part I, berentak in part II, and maranung in part III. Keywords: Bulean, menginang, berentak, maranung